2017
DOI: 10.1111/cns.12697
|View full text |Cite
|
Sign up to set email alerts
|

Sarsasapogenin‐AA13 ameliorates Aβ‐induced cognitive deficits via improving neuroglial capacity on Aβ clearance and antiinflammation

Abstract: The present study indicated that the neuroprotective effect of AA13 might relate to its modulatory effects on microglia activation state, phagocytic ability, and expression of Aβ-degrading enzymes, which makes it a promising therapeutic agent in the early stage of Alzheimer's disease (AD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 44 publications
2
16
0
Order By: Relevance
“…Among microglia, M2 microglia reportedly express NEP and IDE and reduce Aβ plaques (Shimizu et al, ). Recently, there are a few known agents such as PF‐3845, sarsasapogenin‐AA13, and dihydromyricetin, which promoted M2 microglial and inhibited M1 microglial polarization, leading to the memory recovery in traumatic brain injury and AD models (Feng et al, ; C. Huang et al, ; Tchantchou et al, ). Furthermore, dihydromyricetin promoted the clearance of Aβ and expression of NEP in APP/PS1 transgenic mice brain (Tchantchou et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Among microglia, M2 microglia reportedly express NEP and IDE and reduce Aβ plaques (Shimizu et al, ). Recently, there are a few known agents such as PF‐3845, sarsasapogenin‐AA13, and dihydromyricetin, which promoted M2 microglial and inhibited M1 microglial polarization, leading to the memory recovery in traumatic brain injury and AD models (Feng et al, ; C. Huang et al, ; Tchantchou et al, ). Furthermore, dihydromyricetin promoted the clearance of Aβ and expression of NEP in APP/PS1 transgenic mice brain (Tchantchou et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…17 More studies have also shown that its derivatives are effective in anti-inflammatory, neuroprotective, and memory impairment related to aging. 21,22 However, the role of sarsasapogenin in osteoclast formation and bone resorption has not been reported. Thus, the effects of sarsasapogenin on these areas remain to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we synthesised several carbamate derivatives exhibiting neuroprotective and NO production inhibitory properties (Pan, Van Khang, Dong, Wang, & Ma, ). Among all the derivatives, AA13 has emerged as one of the most useful compounds to inhibit inflammatory reactions and ameliorate Aβ‐induced cognitive deficits (Dong et al, ; Huang et al, ). AA13 also shows neuroprotective effect on Alzheimers disease (AD) model by promoting Aβ clearance and shifting pro‐inflammatory M1 to anti‐inflammatory M2 phenotype.…”
Section: Introductionmentioning
confidence: 99%